2000
DOI: 10.1095/biolreprod62.6.1818
|View full text |Cite
|
Sign up to set email alerts
|

Region-Specific Regulation of Cytochrome P450 Aromatase Messenger Ribonucleic Acid by Androgen in Brains of Male Rhesus Monkeys1

Abstract: We demonstrated previously that testosterone regulates aromatase activity in the anterior/dorsolateral hypothalamus of male rhesus macaques. To determine the level of the androgen effect, we developed a ribonuclease protection assay to study the effects of testosterone or dihydrotestosterone (DHT) on aromatase (P450(AROM)) mRNA in selected brain areas. Adult male rhesus monkeys were treated with testosterone or DHT. Steroids in serum were quantified by RIA. Fourteen brain regions were analyzed for P450(AROM) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
17
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 32 publications
7
17
1
Order By: Relevance
“…Similar observations dealing with the regulation of aromatase activity by androgens have been reported in the brain of the rat (Roselli & Resko 1984, Zwain et al 1997, Resko et al 2000. Below a threshold of 100 ng/ml testosterone the Leydig cell increase of estradiol output is the consequence of either post-transcriptional events and/or use of available mRNAs without transcriptional effects (which may indeed explain the slight diminution of the amount of P450arom mRNA; Fig.…”
Section: Discussionsupporting
confidence: 77%
“…Similar observations dealing with the regulation of aromatase activity by androgens have been reported in the brain of the rat (Roselli & Resko 1984, Zwain et al 1997, Resko et al 2000. Below a threshold of 100 ng/ml testosterone the Leydig cell increase of estradiol output is the consequence of either post-transcriptional events and/or use of available mRNAs without transcriptional effects (which may indeed explain the slight diminution of the amount of P450arom mRNA; Fig.…”
Section: Discussionsupporting
confidence: 77%
“…Data have been reported showing a positive role for androgens in aromatase expression in rat testicular somatic cells; these studies were in the presence of a saturating amount of testosterone (200 ng/ml) (Levallet & Carreau 1997, Genissel & Carreau 2001. Moreover in the rat brain (Roselli & Resko 1984) as well as in the brain of male rhesus monkeys (Resko et al 2000) androgens regulate aromatase at both the transcriptional level and the enzyme activity via the presence of ARs (Roselli et al 2001). In male gonad the localization of AR is a subject of controversy (for review see Eddy 2002); some reports have demonstrated the presence of immunoreactive AR in germ cells (Vornberger et al 1994, Zhou et al 1996 and other studies have shown that only testicular somatic cells express AR (Suarez-Quian et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…AR are colocalized in aromatase-positive cells but no estrogen receptor-α (ERα) can usually be detected in most of the cells expressing this enzyme in the POM or BST, although ERα are present in many adjacent cells of the same nuclei. It has been hypothesized that the effects of estrogens on aromatase transcription are mediated transynaptically [79]while androgens may act directly on the aromatase gene [80, 81, 82, 83]. Studies undertaken with in vitro systems have shown that the interactions of SRC-1 with ERα are stronger than with AR but the relative importance of this coactivator for the modulation of both estrogen and androgen receptor action in vivo remains to be determined.…”
Section: Discussionmentioning
confidence: 99%